Pengaruh Variabel Makroekonomi Terhadap Kinerja IHSG: Fokus pada Inflasi dan Suku Bunga (2019-2023) - Asty Ananta; Donella Cleodora Tesalonika; Erwin Giopingki; Felda Indriasari; Heldy Heldo; Kevin Putra Anugrah; Laura Reyna Adelia Sirait; Lusiana Simandalahi; Murny Cahnia; Nadya Azzahra; Novita Sari Simamora; Riska Mawardani; Risnauli Butarbutar; Stefani Mayanglina Sinurat (MES Management Journal, 2025)
This study aims to analyze the effect of inflation and interest rates on the Composite Stock Price Index (JCI) as the main indicator of the capital market in Indonesia in the 2019-2023 period. JCI reflects the dynamics of the stock market which is influenced by various macroeconomic factors. This study uses a quantitative approach with multiple linear regression analysis, utilizing secondary data from the Indonesia Stock Exchange (IDX) and the Central Statistics Agency (BPS). The results showed that inflation has a significant positive effect on the JCI, while interest rates have no significant effect. The classical assumption test ensures that the regression model used is valid and reliable. Based on the analysis, inflation and interest rates together explain 26% of the variability of the JCI, while the rest is influenced by other factors. In conclusion, inflation plays an important role in influencing the JCI, making it a major concern for investors and policymakers.